INCORPORATION OF BACK-PRESSURE EFFECTS IN THE MODELING OF THE PISTON RING/CYLINDER LINER - Palma, Alfredo Jaramillo; Silva, Hugo Checo; Buscaglia, Gustavo Carlos (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The piston ring/cylinder liner system is responsible for about 5% of the energy lose due to friction in a passenger car (Holmberg et al., 2012). Consequently, automotive industry and academy have made efforts seeking for designs that diminish both friction and wear. During the last year, several numerical and experimental studies have shown that texturization can have favorable or detrimental effects on the tribological characteristics of lubricated mechanisms. However, few studies have included the effects of the gas pressure in the combustion chamber, which variates rapidly in the compression stroke and can reach values as high as 60[atm]. Reynolds equation with zero-pressure Dirichlet conditions is mainly adopted in numerical works along with Elrod-Adams cavitation model. This cavitation model only admits a constant cavitation pressure, in spite it is known that cavitation pressure can variate according to the operational conditions (Shen et al., 2013). This work is devoted to the study of the effects that the combustion chamber pressure can have on both the mechanical dynamic of the rings and the cavitation pressure p.